Capillaria appendigera n. sp. (Nematoda: Capillariidae) from the goldbanded jobfish Pristipomoides multidens (Day) (Lutjanidae) and new records of other intestinal capillariids from marine perciform fishes off Australia - Moravec, František; Barton, Diane P (Systematic parasitology, 2018)
Based on light and scanning electron microscopical studies, a new nematode parasite, Capillaria appendigera n. sp. (Capillariidae), is described from the intestine of the goldbanded jobfish Pristipomoides multidens (Day) (Perciformes, Lutjanidae) from the Arafura Sea West, off the northern coast of Australia. The new species, belonging to the subgenus Procapillaria Moravec, 1987, differs from other congeneric species from fishes mainly in the length (0.92-1.13 mm), shape and structure of the spicule, obtuse spines on the spicule sheath and the structure of eggs. It is characterised, in the male, by the presence of two well-developed dorsolateral caudal lobes, a pair of lateral papillae, a heavily sclerotised spicule with many rough transverse grooves covering almost the entice spicule surface (except for spicule ends), a spinose spicule sheath, and in the female, by a subterminal anus, mostly the presence of a large vulval appendage and by eggs (size 54-69 × 27-33 µm) encapsulated by a conspicuous light-coloured superficial layer. Capillaria appendigera n. sp. is the 12th nominal species of capillariids recorded from fishes in Australian waters and the second known capillariid species parasitising fishes of the perciform family Lutjanidae. In addition, four unidentifiable, morphologically different types of capillariid females, probably representing undescribed species, were recorded from the intestines of marine fishes off the northern coast of Australia: Capillariidae gen. sp. 1 and Capillariidae gen. sp. 2 from Lutjanus johnii (Bloch) and L. malabaricus (Bloch & Schneider), respectively (both Lutjanidae), Capillariidae gen. sp. 3 from Protonibea diacanthus (Lacépède) (Sciaenidae) and Capillariidae gen. sp. 4 from Rachycentron canadum (Linnaeus) (Rachycentridae).
Keywords: Capillaria; Austrálie; Perciformes; střeva; druhová specificita; Male; Animals; Intestines; Aquatic Organisms; Female; mužské pohlaví; ženské pohlaví; vodní organismy; zvířata; Species Specificity; Australia